2021
DOI: 10.3390/min11060605
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Carbonate Rocks in a Laboratory Setting: Rates and Textures

Abstract: Determining the dissolution rates of carbonate rocks is vital to advancing our understanding of cave, karst, and landscape processes. Furthermore, the role of carbonate dissolution is important for the global carbon budget and climate change. A laboratory experiment was setup to calculate the dissolution rates of two whole rock carbonate samples with different petrographic makeup (ooids and brachiopods). The carbonate rock samples were also explored under a scanning electron microscope to evaluate the textures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…First of all, it concerns the estimation of cavity growth rate in soluble rocks (i.e., their dissolution rate), which has recently been persistently cultivated as a necessary element of karst hazard assessment [17]. This criterion has not been evaluated for two reasons: firstly, it is meaningless in relation to limestones that have very low dissolution rates, and secondly, such an evaluation can only be correctly carried out experimentally in the field [18] or laboratory [19], which in these circumstances is difficult and time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, it concerns the estimation of cavity growth rate in soluble rocks (i.e., their dissolution rate), which has recently been persistently cultivated as a necessary element of karst hazard assessment [17]. This criterion has not been evaluated for two reasons: firstly, it is meaningless in relation to limestones that have very low dissolution rates, and secondly, such an evaluation can only be correctly carried out experimentally in the field [18] or laboratory [19], which in these circumstances is difficult and time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonate dissolution is comparatively faster than the residence time of water in the karst (saturation achieved in a few hours up to several days [88][89][90], so that equilibrium between CO 2 dissolved in the water and Ca 2þ ions should be always attained irrespective of the hydrological conditions (except possibly for drip sites dominated by fracture flow following heavy rainfall).…”
Section: Methodsmentioning
confidence: 99%
“…Karst has received more and more attention from international scholars, and s research results have been achieved on carbonate rock dissolution experiments, which mainly focused on indoor simulation experiments. For example, Li, N.Y. et al [13], L et al [14], and Hyunsang et al [15] simulated the dissolution reaction indoors by usi rock disk rotating and moving relative to the solution; Erik B. Larson et al [16], in indoor study of carbonate dissolution rates, found that the petrography and minera of carbonate rocks affect their dissolution rates in a laboratory setting; Plummer et al found large differences in calcite dissolution rates and their mechanisms of change un different pCO2 conditions by studying the kinetic mechanisms of calcite dissolution doors; Yu, S. et al [18] showed that the dissolution rate of carbonate rocks was affecte rainwater acidity and rainfall via an experimental indoor dissolution study of carbo Karst has received more and more attention from international scholars, and some research results have been achieved on carbonate rock dissolution experiments, which are mainly focused on indoor simulation experiments. For example, Li, N.Y. et al [13], Li, Q. et al [14], and Hyunsang et al [15] simulated the dissolution reaction indoors by using a rock disk rotating and moving relative to the solution; Erik B. Larson et al [16], in an indoor study of carbonate dissolution rates, found that the petrography and mineralogy of carbonate rocks affect their dissolution rates in a laboratory setting; Plummer et al [17] found large differences in calcite dissolution rates and their mechanisms of change under different pCO 2 conditions by studying the kinetic mechanisms of calcite dissolution indoors; Yu, S. et al [18] showed that the dissolution rate of carbonate rocks was affected by rainwater acidity and rainfall via an experimental indoor dissolution study of carbonate rocks by acid rain in Guilin, China.…”
Section: Introductionmentioning
confidence: 99%